Beliefs about dental whitening among dental students and Dentists (Research, Society and Development, 2022)
Objective: to verify and compare the level of information about tooth whitening among dental students and Dentists. Materials and methods: 29 academics and 39 dentists (CD) participated of the research. A remote questionnaire was applied containing questions related to the use of LED device, white diet, reservoirs in the whitening tray, anti-inflammatory drugs, "over the counter" whitening, the possibility of performing whitening in patients who are still undergoing orthodontic treatment, the time interval indicated between whitening appointments and the time for replace the restorations after the end of the whitening treatment. The data obtained were analyzed in a descriptive way and through the application of the t test (α = 0.05).Results: For most questions, similar answers were obtained between the two groups, except for the questions regarding the time interval indicated between in-office whitening appointments (p < 0.01); regarding the use of anti-inflammatory drugs prior to this procedure in order to reduce postoperative sensitivity (p < 0.01); and about the time needed to replace the dental restorations after the end of the treatment (p < 0.01). Conclusion: the research showed that many "myths" about tooth whitening are still widespread, such as the impossibility of whitening the teeth of patients who still undergo conventional orthodontic treatment and the need of a white diet. Those beliefs must be demystified to conduct evidence-based dentistry.